Colonialism, development, and the environment - Das, Pallavi V. (New York, NY)
xix, 189 sayfa
Keywords: “This book focuses on the colonial encounter between Britain and India in the field of economic development, including scientific/technological changes, and the environmental impact of this encounter on India. Through the institutions of the colonial state, Das argues, the metropole (Britain) initiated economic development strategies in the colony (India) in order to efficiently extract resources from it. While colonial encounters have been seen by scholars more or less in economic and political terms, what is largely missing is the fact that the metropole's economic development strategies had definite ecological consequences for the colony. This book aims to fill that gap with an examination of how the railways led to deforestation in colonial India. The deforestation, in turn, put at risk the entire project of railway expansion. This led to state implementation of forest conservation. Conservation, however, was also an economic-developmental project whose main aim was to maintain timber supplies for the railways rather than care for ecological concerns. Thus the history of colonialism has both economic (and political) as well as ecological dimensions“ --